(untitled) (Revista Contexto & Saúde, 2026)
Chronic kidney disease (CKD) is a serious condition with an increasing number of cases and a significant impact on oral and systemic health, with xerostomia being the most prevalent oral alteration. This study aimed to analyze xerostomia and hyposalivation in two groups (Hemodialysis and Healthy) and to relate these parameters to the decayed, missing, and filled teeth index (DMFT). This is an observational study involving 80 patients. The treatment group was referred from two hemodialysis centers in Recife, while the Healthy group had no CKD and was recruited from the Stomatology Clinic of the Federal University of Pernambuco (UFPE). DMFT index, salivary flow, and xerostomia data were recorded. In the Hemodialysis group, 15% of the patients presented hyposalivation, with a statistically significant difference compared to the Healthy group (p = 0.038). Xerostomia was reported by 20% of patients in the Hemodialysis group and 10% in the Healthy group, and the presence of caries occurred in 62.5% of the Hemodialysis group, with no statistically significant differences between groups. In this study, hyposalivation was more prevalent in patients with chronic kidney disease. However, it was not possible to relate hyposalivation and xerostomia to the DMFT index. Attention should be given to these patients so that medical treatments can be carried out without impediments due to dental causes.